Optimizing Sumatera Utara’s Economic Growth through a Maqashid Sharia Approach to Unemployment, Human Development Index - Putra , Muhammad Umar Maya; Marpaung, Muslim; Rahmanta, Rahmanta; Tampubolon, Arsyaf; Lestari, Dwi Vita; Soehardi, Soehardi (LLDIKTI Wilayah 1 Sumatera Utara, 2025)
Poverty, unemployment, and human development are closely intertwined and remain persistent challenges in Indonesia, particularly in the wake of the COVID-19 pandemic. This study investigates the influence of unemployment, economic growth, and the Human Development Index (HDI) on poverty in Indonesia over the period 2013–2024, using 48 quarterly observations sourced from Statistics Indonesia (BPS). Anchored in Islamic economic thought, the analysis incorporates the concept of maslahah. The pursuit of public benefit and welfare as a normative foundation for development. A quantitative method is employed using the Error Correction Model (ECM), which enables the examination of both short-term fluctuations and long-term relationships among variables. The results show that, in the short term, rising unemployment significantly exacerbates poverty, while in the long term, improvements in economic growth and HDI are effective in alleviating poverty levels. These findings highlight the need for integrated and sustained efforts to enhance human capital, generate employment, and ensure inclusive economic progress. Policy frameworks inspired by maslahah can help ensure that anti-poverty strategies are not only economically effective but also ethically grounded, thereby supporting the broader objectives of the Sustainable Development Goals (SDGs).